Light-Trap Catch of Moth Species (Lepidoptera) in Connection with the Retention Time of the Moon above Horizon - Nowinszky L; Puskás J; Kiss M (International Journal of Entomology, 2020)
The study deals with light trapping of moths in connection between retention time of the Moon above horizon. The authors suggest the retention time is an independent of the lunar phase and a stationary characteristic of the effect of the Moon on the result of light trapping.
Keywords: Light-trap